2018
DOI: 10.1167/iovs.17-23203
|View full text |Cite
|
Sign up to set email alerts
|

Local Progression Kinetics of Geographic Atrophy in Age-Related Macular Degeneration Are Associated With Atrophy Border Morphology

Abstract: PURPOSE.To assess the impact of distinct atrophy border characteristics based on spectraldomain optical coherence tomography (SD-OCT) imaging on local atrophy progression. METHODS.Patients with geographic atrophy (GA) secondary to AMD were recruited in the context of the Longitudinal Fundus Autofluorescence in Age-related Macular Degeneration and Directional Spread in Geographic Atrophy studies (NCT00393692, NCT02051998). Horizontal and vertical SD-OCT scans were acquired at sequential visits using a device al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Our proposed metrics of photoreceptor degeneration may be helpful in future clinical trials in patients with GA as an additional biomarker for patient selection/stratification or even as a structural, objective clinical end point. Previously, imaging features related to lesion shape (lesion size, lobularity, and focality), RPE-associated characteristics (FAF patterns), junctional-zone configuration in SD-OCT, and optical coherence tomography angiography (OCTA)–based choriocapillaris flow-signal voids were shown to be prognostic for atrophy progression. Moreover, a qualitative study by Nunes et al, based on a en face projection centered to the EZ, suggested an association of photoreceptor degeneration with future atrophy progression.…”
Section: Discussionmentioning
confidence: 99%
“…Our proposed metrics of photoreceptor degeneration may be helpful in future clinical trials in patients with GA as an additional biomarker for patient selection/stratification or even as a structural, objective clinical end point. Previously, imaging features related to lesion shape (lesion size, lobularity, and focality), RPE-associated characteristics (FAF patterns), junctional-zone configuration in SD-OCT, and optical coherence tomography angiography (OCTA)–based choriocapillaris flow-signal voids were shown to be prognostic for atrophy progression. Moreover, a qualitative study by Nunes et al, based on a en face projection centered to the EZ, suggested an association of photoreceptor degeneration with future atrophy progression.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a severity classification based on fundus photography was developed 16 . Again, OCT angiography was not included in classification systems as yet, although a wide variety of studies indicate that choroidal perfusion abnormalities are associated with the risk of disease progression [225][226][227][228][229] .…”
Section: Potential Challengesmentioning
confidence: 99%
“…Conceptually related to the FAF phenotype, it was shown that patients with severe junctional zone abnormalities at the GA boundary in SD‐OCT, photoreceptor thinning outside of GA and reticular pseudodrusen, or hyperreflective foci exhibit a faster atrophy progression rate (Lindner et al., 2018; Pfau, Möller, Künzel, et al., 2020; Pfau, von der Emde, de Sisternes, et al., 2020; Pfau, von der Emde, Dysli, et al., 2020; Reiter et al., 2020; Schmidt‐Erfurth et al., 2020).…”
Section: Artificial Intelligence In Geographic Atrophymentioning
confidence: 99%